Analysis of rain fade mitigation using site diversity on earth-to-satellite microwave links at Ku-Band - Islam, Md. Rafiqul; Muhammad, Norhafizah; Singh, Mandeep; Lwas, Ali K.; ., Robiatul Adawiyah; Ismail, Ayunie (2014)
Rain is the major challenge to design reliable earth to satellite microwave link at higher frequencies in tropical regions. Site diversity is one of the techniques used to mitigate this problem. Hodge Site Diversity Gain Model, ITU-R Site Diversity Gain Model and ITU-R Diversity Improvement Factor Model are analyzed based on rainfall data measured in Malaysia and four locations in Kuala Lumpur and MEASAT3A as reference satellite. In analysis, it is found that significant improvement in availability can be achieved through the site separations of 6 to 37 Km in site diversity technique.